ANALISIS EKONOMI KAWASAN WISATA TAMAN NASIONAL GUNUNG GEDE PANGRANGO KECAMATAN CIPANAS KABUPATEN CIANJUR - James Sinurat; Dewi Fitrianti (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2016)
ABSTRACT The objectives of this research are: (1) To know the contribution of the National Park of Pangrango Gede Mountain to the peoples income of Cimacan Village, District Cipanas, Cianjur Regency; (2) To know the contribution of infrastructure and facilities of the National Park of Pangrango Gede Mountain to the peoples income of Cimacan Village, District Cipanas, Cianjur Regency; and (3) To know the contribution of promotion of the National Park of Pangrango Gede Mountain to the peoples income of Cimacan Village, District Cipanas, Cianjur Regency. Data analysis methods used are: 1) Analysis data test (normality, multicolinearity, heteroskedasticity and autocorrelation); 2) Test regression and correlation using SPSS to see the effect of attraction management of the Natonal Park of Pangrango Gede Mountain against peoples income of Cimacan Village, District Cipanas, Cianjur Regency. The results showed that: 1) The attractions of the Natonal Park of Pangrango Gede Mountain has significant effect on public revenues of Cimacan Village, District Cipanas, Cianjur Regency; 2) Infrastructure and facilities of the National Park of Pangrango Gede Mountain have significant effect on peoples income of Cimacan Village, District Cipanas, Cianjur Regency; 3) Promotion of attraction management of the National Park of Pangrango Gede Mountain has real impact on peoples income of Cimacan Village, District Cipanas, Cianjur Regency. Keywords: People's Income, Infrastructure and Facilities, and Promotion of Tourism Object